Identification and characterization of chalcone synthase cDNAs (NnCHS) from Nelumbo nucifera - Dong, C; Yu, A Q; Wang, M L; Zheng, X W; Diao, Y; Xie, K Q; Zhou, M Q; Hu, Z L (Cellular and Molecular Biology, 2015)
Chalcone synthase (CHS) catalyzes the first committed step in flavonoids biosynthetic pathway. In this study, six full-length cDNAs (NnCHS) encoding CHS from Nelumbo nucifera were successfully isolated, using rapid amplification cDNA end (RACE) assay. The obtained cDNAs were 1426 bp in size, containing a 1167 bp open reading frame coding 389 amino acids. Exons-intron architecture of NnCHS gene was illustrated, consisting two exons inserted by a 426 bp intron. The putative NnCHS possessed all the conserved active sites for CHS function as well as the family signature. Phylogenetic analysis revealed that NnCHS shared high homology with CHS from high plants, and the homology-based structural modeling showed that NnCHS had the typical structure of CHS. Moreover, Real-time PCR assays demonstrated that NnCHS mRNAs were expressed in various tissues of N. nucifera, with the highest expression in red flower and lowest level in the leaves. Moreover, patterns of NnCHS expression illustrated short-time wounding or low temperature significantly induced the up-regulation of NnCHS mRNA.